Effects of 12-week pilates reformer training on the biomechanics of Latin dance Cha-Cha circle chasing technique - Che, Li; Zhou, Yijia; Wang, Ying (Frontiers in Physiology, 2025)
BackgroundPilates Reformer training is a scientifically validated method for enhancing body control. However, research on its application to improve the technical quality of Latin dance movements, particularly the Cha-Cha circular chase step, is limited. This study aims to evaluate the effectiveness of Pilates Reformer training in enhancing this technique, with the goal of providing a theoretical foundation for its use in improving Latin dance performance and preventing injuries.MethodsOur study involved 18 Latin dance students specializing in sports dance, aged 18–30 years, with at least 3 years of Latin dance experience. Participants were randomly assigned to an experimental group (n = 9) and a control group (n = 9). Over a 12-week period, the experimental group underwent Pilates Reformer training, while the control group continued with their regular training. Biomechanical data were collected before and after each session to assess joint angles, movement speed, muscle activation, and technical quality scores using the WDSF 3.0 evaluation criteria. Data analysis and visualization were performed using Graph Prism 10.0 software, and statistical analyses were conducted with SPSS software (Version 22). Paired-sample t-tests were used for within-group comparisons, and independent-sample t-tests were used for between-group comparisons, with a significance level set at p < 0.05.Results(1) The experimental group showed significant (P < 0.05) or highly significant (P < 0.01) differences in the joint angles of the hip, knee, and ankle at key points across all three axes (X, Y, Z) compared to the control group. The experimental group also exhibited significant improvements (P < 0.05) in the flexion and extension speeds of these joints during the movement phases, while the control group showed minimal changes (P > 0.05). (2) Pilates Reformer training led to significant increases (P < 0.05 or P < 0.01) in the RMS normalized muscle activation values in both legs during the Cha-Cha circular chase step. In contrast, the control group showed increased iEMG values, but these did not reach statistical significance (P > 0.05). (3) The experimental group showed significant improvements (P < 0.05) in posture (B1), foot movements (B4), and Latin characteristics (B5), as well as highly significant improvements (P < 0.01) in basic movements (B6) and preparation-action-recovery (B7) compared to the control group. Additionally, the experimental group exhibited consistent improvements in the average TQ scores across all evaluated components.ConclusionPilates Reformer training significantly enhances joint angles, movement speeds, muscle activation, and technical quality in Latin dance, particularly the Cha-Cha circular chase step. These findings demonstrate the potential of Pilates Reformer training to improve dance technique, optimize movement quality, and support injury prevention in Latin dance athletes, providing strong evidence for its effectiveness in this domain.